PENGARUH SELF COMPASSION DENGAN BODY DISSATISFACTION PADA MAHASISWA ABI FISB IWU - LUSIANA, VINA; SAPUTRA, BANYU (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2024)
Body Dissatisfaction problems are caused by wrong views and self-judgments. This assessment usually takes the form of a view that the individual has experienced weight gain which causes their body to deviate from the image of the